Avaliação do processo de reparação tecidual após Exérese realizada com bisturi convencional e bisturi harmônico Harmonic® de necrose induzida em língua de rato: estudo macroscópico e histológico - Achkar, Vivian Narana Ribeiro El [UNESP] (2014)
The Harmonic® scalpel (HS) was shown in surgical practice for more than a decade, with the aim of minimizing the risks of electro-surgical technologies, local energy damage and/or peripheral, in addition to complications associated with monopolar energy. Characterize by the conversion of electrical energy into mechanical energy leading to active blade vibration of 55,500 Hz per second producing a secondary heating which promotes the formation of a blood clot while cutting, adhesive sealing veins and lymphatic vessels of up to 5 mm in diameter. Contributes to the reduction of the time of surgery, postoperative pain and blood loss with lower temperatures when compared to electric scalpel and high-power lasers radiation. Considering the several advantages attributed to HS and the paucity of literature regarding was deemed necessary a study that evaluates the parameters on tissue repair of surgical treatment with HS when compared with the conventional scalpel (CS), taking into account the stages of tissue repair in the tongue. For that a necrosis induction of lateral border of tongue was held in 18 rats divided into 2 groups for surgical removal of the lesion with HS and CS. Three rats per group were sacrificed at 7, 14 and 28 days and subjected to macroscopic and microscopic analyses. Despite the clinical and histological differences observed in early times and in the end, the quality of the repair process was similar in both groups